Selective Electroless Precipitation Of Copper On Non - Conductive Surfaces Using The Semiconductor Zinc Oxide. - Mohsin Uraibi (University of Thi-Qar Journal of Science, 2019)
Zinc oxide layer being thermally precipitated on glass and ceramicstrips ( 2x2.5 cm ) before the electroless precipitation of copper utilizingthe conventional Printed Circuit Boards( PCB) technologies inconjunction with the required modifications to optimize the quality of these layers . The roughness of ZnO films was Ra 0.02 µm and its thickness about 0.7µm. The films being characterized by X- ray diffraction . The bivalentPd( І І ) used as activator was reduced to Pd (0) on surface of ZnO layerby UV light in 1.5 – 2 minutes intervals . Copper lines precipitated in the subsequent steps have an adhesionpower of 2and 5 kg.mm-2 on glass and ceramic respectively . The specific conductance of the electrolessly deposited copper was found to be( 5.3x106)ohm-1.cm-1, and the resistivity was ( 1.8 x10 -6)ohm.cm . From theresults of this study the method could be utilized in PCB fabrication